From Grassroots to Glory: The Justice of Sports Infrastructure in Indonesia’s Local Communities (Indonesian Sports Justice Review, 2024)
Access to quality sports infrastructure is a fundamental issue in ensuring equitable opportunities for athletes in Indonesia. This paper explores the justice of sports infrastructure, focusing on the disparities between urban and rural areas in terms of sports facilities and access to athletic training. The study assesses how the lack of infrastructure in local communities limits the potential of young athletes and hinders the development of sports at the grassroots level. Drawing on field research from multiple regions, the paper investigates how government policies, public investment, and private sector involvement have shaped sports infrastructure development. It also considers how local communities can be empowered to advocate for better facilities and support for grassroots sports. The paper advocates for a more equitable distribution of sports infrastructure and the creation of policies that prioritize community-based sports programs, aiming to provide opportunities for all athletes, regardless of their socio-economic background.